Experimental investigation of a multilayer nitride coating deposited on austenitic coating steel. (2023) - Jasper, S.; Vijayakumar, D.; Stalin, B.; Rajesh, S.; Jhansi Ida, S.
Abstract: Friction is the drawback in automotive and industrial machining parts and assembly. To overcome the wear loss due to friction the surface property must be enhanced using suitable technology. Arc deposition is a PVD type of coating which improves the property such as hardness, roughness, corrosion, and tribological on a server work environment. Titanium nitride (TiN) and titanium aluminum nitride (TiAlN) are hard ceramic coating materials. The mechanical and wear properties of stainless steel (SS304) coated with Method of cathodic arc deposition (CAD) The ability to slide against Ti–6Al–4 V alloy has improved significantly. The three coated samples' surface hardness, roughness, and wear rate are measured and compared. The applied tension (2–6 N), sliding velocity (0.32–0.75 m/s), and sliding distance (580–1500 m) tribological parameters are modified during the wear test with the ball-on-disc. In comparison to other types of coatings, On the SS316L surface, the TiN coating provides exceptional mechanical and tribological properties.